A Case Study on OPD Level Management of Infertility due to PCOS with Ayurvedic Medicines (International Journal of Ayurveda and Pharma Research, 2023)
PCOS is the primary cause of Hyperandrogenism and oligo-ovulation at the reproductive age and is often associated with infertility. The prevalence of infertility in women with PCOS varies between 70 and 80 %. In Ayurveda, Vandhyatva is considered as one among the Rasa pradoshaja vikaras. This is case report of an infertile couple who had not been able to conceive since 4 yrs. The wife was diagnosed with PCOS. Based on the parameters of Ayurvedic science this case was diagnosed as Vandhyatva (infertility) due to Nashtarthava (PCOS). The treatment plan for PCOS is to correct the menstrual irregularity and ensure proper ovulation, this itself helps to develop healthy progeny and successful childbirth. The treatment principles selected here were mild Shodhana and Samana therapy especially Vatakaphahara, Agni deepana along with Pathya ahara. After two and half month of internal medications, reduction in abnormal hair growth, blackish discolouration and weight were noticed. The outcome of the treatment resulted in natural conception and delivered a full term male baby. So this case signifies effect of Ayurvedic science in the management of infertility.